Réponses

2014-06-01T19:07:11+02:00
Soit l'expression E = (2x+3)² - (4x-1)(2x+3)
E = 4x² + 12x + 9 - (8x² + 12x - 2x - 3)
E = 4x² +12x +9 - 8x² -12x + 2x +3
E = - 4x² +2x + 12

b) E = (2x+3)(2x+3 -4x +1)
E = (2x+3)(-2x +4)

c) pour x = -3
(-6  +3)( 6 +4) = -3 x 10 = -30

d) e = 0
soit 2x +3 = 0
2x = -3
x = -3/2

soit -2x +4 = 0
-2x = -4
x = 2

2014-06-01T19:13:33+02:00
a)
E = (2x+3)² - (4x-1)(2x+3)
   =(2x)²+2*2x*3+3²-(4x*2x+4x*3-1*2x-1*3)
   =4x²+12x+9-(8x²+12x-2x-3)
  =
4x²+12x+9-(8x²+10x-3)
  =4x²+12x+9-8x²-10x+3
  =-4x²+2x+12

b)
E = (2x+3)² - (4x-1)(2x+3)
   =(2x+3)(2x+3)-(4x-1)(2x+3)
   =(2x+3)(2x+3-4x+1)
  =(2x+3)(-2x+4)

c)
E=(2x+3)(-2x+4)
  =(2*(-3)+3)(-2*(-3)+4)
  =-3*10
  =-30

d)
(2x+3)(-2x+4)=0
Un produit est nul si et seulement si un des facteurs est nul.
2x+3=0
2x=-3
x=-3/2

ou

-2x+4=0
-2x=-4
x=-4/-2
x=2

voilà :)